Model for implementation of green construction / Afzan Ahmad Zaini - Ahmad Zaini, Afzan (Institute of Graduate Studies, UiTM, 2017)
The recent shift from conventional construction to green construction has brought about efficiency and improvement to the construction industry. However, the construction industry is still reluctant to embrace this new development. This circumstance is primarily due to a fundamental problem of the lack of clarity in grasping the concept of green construction. Consequently, it has called for a need to explore the current practice of green construction in the construction industry with which this research has attempted to deal. In this research, a considerable effort was made towards identifying the solution to the problem through the establishment of a green construction model. In the process of establishing the model, four objectives were outlined; (1) To identify the current practice of green construction, (2) To investigate the level of awareness and understanding of the benefits and disadvantages of green construction, (3) To investigate factors of green construction innovation, and (4) To determine the major challenges for the implementation of green construction. The findings used for the establishment of the model were structured and analysed based on the data from 346 usable questionnaires and 25 semi-structured interviews with the aid of SPSS19 and NVivo-9 respectively…